Concentração espacial e especialização do mercado de trabalho formal do Rio Grande do Norte no período (2000-2010) - Araújo, Ambrósio Silva de (2013)
The aim of this study was to analyze the spatial concentration of economic specialization in Rio Grande do Norte. The analysis variable was the number of formal jobs in 2000 and 2010 obtained from the Annual Social Information - RAIS, provided by the Ministry of Labor and Employment - MTE. To achieve this objective we have used instruments of regional analysis, more precisely the location quotient and coefficient of specialization. The analysis of the coefficients showed strong spatial concentration/spatial location of some economic activities within certain micro. Another aspect observed was the very strong presence of the economic sector of public administration in quantitative formal jobs each micro as well as the growth of the trade and services, respectively, in line with what also occurred in Brazil.